Optimal. Leaf size=28 \[ \frac {2 x}{x-x^2}+\frac {4 \log ^{e^{2 x} x}(3)}{x} \]
________________________________________________________________________________________
Rubi [A] time = 0.69, antiderivative size = 51, normalized size of antiderivative = 1.82, number of steps used = 5, number of rules used = 4, integrand size = 65, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.062, Rules used = {1594, 27, 6688, 2288} \begin {gather*} \frac {2}{1-x}+\frac {4 e^{2 x} (2 x+1) \log ^{e^{2 x} x}(3)}{x \left (2 e^{2 x} x+e^{2 x}\right )} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
Rule 27
Rule 1594
Rule 2288
Rule 6688
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int \frac {2 x^2+\log ^{e^{2 x} x}(3) \left (-4+8 x-4 x^2+e^{2 x} \left (4 x-12 x^3+8 x^4\right ) \log (\log (3))\right )}{x^2 \left (1-2 x+x^2\right )} \, dx\\ &=\int \frac {2 x^2+\log ^{e^{2 x} x}(3) \left (-4+8 x-4 x^2+e^{2 x} \left (4 x-12 x^3+8 x^4\right ) \log (\log (3))\right )}{(-1+x)^2 x^2} \, dx\\ &=\int \left (\frac {2}{(-1+x)^2}+\frac {4 \log ^{e^{2 x} x}(3) \left (-1+e^{2 x} x (1+2 x) \log (\log (3))\right )}{x^2}\right ) \, dx\\ &=\frac {2}{1-x}+4 \int \frac {\log ^{e^{2 x} x}(3) \left (-1+e^{2 x} x (1+2 x) \log (\log (3))\right )}{x^2} \, dx\\ &=\frac {2}{1-x}+\frac {4 e^{2 x} (1+2 x) \log ^{e^{2 x} x}(3)}{x \left (e^{2 x}+2 e^{2 x} x\right )}\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.11, size = 49, normalized size = 1.75 \begin {gather*} -\frac {2}{-1+x}+\frac {4 e^{2 x} (1+2 x) \log ^{e^{2 x} x}(3)}{x \left (e^{2 x}+2 e^{2 x} x\right )} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.63, size = 29, normalized size = 1.04 \begin {gather*} \frac {2 \, {\left (2 \, {\left (x - 1\right )} \log \relax (3)^{x e^{\left (2 \, x\right )}} - x\right )}}{x^{2} - x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [F] time = 0.00, size = 0, normalized size = 0.00 \begin {gather*} \int \frac {2 \, {\left (x^{2} + 2 \, {\left ({\left (2 \, x^{4} - 3 \, x^{3} + x\right )} e^{\left (2 \, x\right )} \log \left (\log \relax (3)\right ) - x^{2} + 2 \, x - 1\right )} \log \relax (3)^{x e^{\left (2 \, x\right )}}\right )}}{x^{4} - 2 \, x^{3} + x^{2}}\,{d x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.13, size = 23, normalized size = 0.82
method | result | size |
risch | \(-\frac {2}{x -1}+\frac {4 \ln \relax (3)^{x \,{\mathrm e}^{2 x}}}{x}\) | \(23\) |
norman | \(\frac {-2 x +4 \,{\mathrm e}^{x \,{\mathrm e}^{2 x} \ln \left (\ln \relax (3)\right )} x -4 \,{\mathrm e}^{x \,{\mathrm e}^{2 x} \ln \left (\ln \relax (3)\right )}}{x \left (x -1\right )}\) | \(39\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.50, size = 29, normalized size = 1.04 \begin {gather*} \frac {2 \, {\left (2 \, {\left (x - 1\right )} \log \relax (3)^{x e^{\left (2 \, x\right )}} - x\right )}}{x^{2} - x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 0.38, size = 22, normalized size = 0.79 \begin {gather*} \frac {4\,{\ln \relax (3)}^{x\,{\mathrm {e}}^{2\,x}}}{x}-\frac {2}{x-1} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.21, size = 20, normalized size = 0.71 \begin {gather*} - \frac {2}{x - 1} + \frac {4 e^{x e^{2 x} \log {\left (\log {\relax (3 )} \right )}}}{x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________